Reconstruction of medial upper lip defect with Abbe flap - Dini Widiarni Widodo; Wulan Mega Gustria (PERHATI-KL, 2022)
ABSTRACTBackground: Reconstruction of upper lip defect is challenging, because the upper lip is formed by two lateral nasolabial subunits and one philtrum subunit. The most effective reconstruction approach for upper lip deformities is still being debated. Purpose: To report a case of upper lip defect, and review the Abbe flap and Estlander flap methods for upper lip reconstruction. Case report: A 62 years old female subject with full thickness defect of two third of the upper lip, repaired by Abbe flap. Clinical question: What is the best surgical preference for upper lip defect reconstruction? Review method: A systematic literature search based on clinical questions, inclusion, and exclusion criteria in the PubMed, ProQuest, EBSCO databases, Scopus and hand searching using keywords. Result: No eligible studies were pertinent to answer the clinical question. Conclusion: Reconstruction options of upper lip defect were based on thickness, size and the defect in the structure involved. The Abbe flap can be used to reconstruct the full thickness medial upper lip, one-third up to two-thirds of the defect area. Lateral defects and commissure involvement can be repaired by Estlander flap. ABSTRAKLatar belakang: Rekonstruksi defek bibir atas lebih sulit, karena dibentuk oleh dua subunit nasolabial lateral dan satu subunit filtrum. Pendekatan rekonstruksi yang paling efektif untuk kelainan bentuk bibir atas masih diperdebatkan. Tujuan: Untuk menyajikan kasus defek bibir atas, pilihan terapi untuk pasien ini dan meninjau pilihan metode operasi dengan jabir Abbe dan Jabir Estlander untuk rekonstruksi bibir atas. Laporan kasus: Seorang wanita 62 tahun dengan defek dua pertiga bibir atas dengan ketebalan penuh, yang direkonstruksi dengan jabir Abbe. Pertanyaan klinis: Apakah pilihan bedah rekonstruksi terbaik untuk defek bibir atas? Telaah literatur: Pencarian literatur sistematis berdasarkan pertanyaan klinis, kriteria inklusi dan eksklusi di database PubMed, ProQuest, EBSCO host dan pencarian tangan menggunakan kata kunci. Hasil: Tidak didapati studi yang memenuhi syarat untuk menjawab pertanyaan klinis. Kesimpulan: Pilihan rekonstruksi untuk defek bibir atas adalah berdasarkan ketebalan, luas, dan kecacatan pada struktur yang terlibat. Jabir Abbe dapat digunakan untuk rekonstruksi medial bibir atas dengan ketebalan penuh sepertiga hingga dua pertiga dari area defek. Defek lateral dan keterlibatan komisura dapat diperbaiki dengan jabir Estlander.